Zasada powszechności elektronicznej administracji - Błażewski, Maciej (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The principle of commonness of e-government is a principle of law, which is expressed in Polish law and in the law of European Union. This principle covers two aspects including the transmission and storage of information by electronic means. The provisions differentiate the scope of the principle of commonness of e-government by the object (the addressee, the sender, the administrator) and the subject of the information.
Keywords: principle of law; e-government; public authority; electronic means of communication